Perlindungan Hak Anak Sebagai Korban Tindak Pidana Persetubuhan dalam Penyelidikan : (Studi di Kepolisian Resort Kota Batu) - Fachry Ahsany; Sidik Sunaryo; Yaris Adhial Fajrin (Indonesia Law Reform Journal, 2022)
This research was to determine the form of providing protection for children's rights as victims of the crime of sexual intercourse during the investigation stage. This study uses a sociological juridical method with an empirical legal approach that describes the actual conditions that live in society. Data was collected by direct observation at the Criminal Investigation Unit of the PPA Police of the Batu City Resort Police, interviews with investigators and other related parties. The data analysis technique is the investigation of children's rights as victims of criminal acts of sexual intercourse based on Law no. 11 of 2012 concerning the Juvenile Criminal Justice System. The results of this study are that in the investigation process there are still obligations for children's rights that are not given or fulfilled, such as children being free from treatment that demeans their dignity and getting social advocacy assistance from child social workers during examinations at the police to determine physical, psychological and psychosocial conditions. The child is a victim of a crime of sexual intercourse.